Group-specific identification of polioviruses by PCR using primers containing mixed-base or deoxyinosine residue at positions of codon degeneracy. - Kilpatrick, D R (1996)
We have developed a method for differentiating polioviruses from nonpolio enteroviruses using PCR. A pair of panpoliovirus PCR primers were designed to match intervals encoding amino acid sequences within VP1 that are strongly conserved among polioviruses. The initiating primer hybridizes with codons of a 7-amino-acid sequence that has been found only in polioviruses; the second primer matches codons of a domain thought to interact with the cell receptor. The panpoliovirus PCR primers contain mixed-base and deoxyinosine residues to compensate for the high degeneracy of the targeted codons. All RNAs from 48 vaccine-related and 110 wild poliovirus isolates of all three serotypes served as efficient templates for amplification of 79-bp product. None of the genomic sequences of 49 nonpolio enterovirus reference strains were amplified under equivalent reaction conditions. Sensitivities of poliovirus detection were as low as 100 fg (equivalent to approximately 25,000 genomic copies or 25 to 250 PFU) when the amplified products were visualized by ethidium bromide fluorescence. These degenerate PCR primers should aid in the detection of all polioviruses, including those wild poliovirus isolates for which genotype-specific reagents are unavailable.